Gait improvement in adults with hemiparesis using a rolling cane: A cross-over trial - Thierry Deltombe; Mie Leeuwerck; Jacques Jamart; Anne Frederick; Geoffroy Dellicour (Medical Journals Sweden, 2020)
Objective: To assess the changes in gait parameters in adults with hemiparesis using a rolling cane (quadripod cane with small wheels; Wheeleo®) compared with a classical quadripod cane. Design: A prospective, multicentric, cross-over randomized trial. Participants: Thirty-two ambulatory adults with hemiparesis. Methods: Participants were assessed using a quadripod cane and a rolling cane. Outcome measures were changes in: walking speed during a 10-m walk test and a 6-min walk test; frequency of 2-step gait; physiological cost index; number of therapist interventions to control the balance; perceived exertion; and participant satisfaction. Results: The following outcomes were improved with the use of a rolling cane: walking speed during a 10-m walk test at comfortable (+22%: p<0.001) and maximal (+30: p<0.001) speeds; walking speed (+50%: p<0.001) and distance (+49%: p<0.001) during a 6-min walk test; and the frequency of 2-step gait. The physiological cost index, perceived exertion, and number of therapist interventions to control the balance remained unchanged. Participant satisfaction improved. Conclusion: A rolling cane, Wheeleo®, increases walking speed in adults with hemiparesis without additional risk of falls.